Anyone seen a sisal stripper? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Alan Chadborn at the Design Centre, c/o WAM, PO Box 50, Katakwi, Uganda enquires 'about methods of treating sisal to protect it from rotting. The ropes made here traditionally by hand are mostly used for tethering animals whilst grazing. They get...